2022
DOI: 10.47205/plhr.2022(6-iii)23
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychological Contract Breach and Psychological Contract Violation: The interactive effects of Tenure

Abstract: The purpose of this study is to examine the relationship between psychological contract breach (PCB) and psychological contract violation (PCV), and the extent to which this relationship is moderated by tenure. The data for the study was collected from a sample of 304 faculty members working in three public-sector universities in Quetta City. Data were collected from respondents using proportionate random sampling and using close-ended questionnaires. The analysis of the data revealed that PCB had a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This study further concluded that participants' satisfaction with the one-sided exploitation in one of games also declined with age (Matsumoto & Yamagishi, 2016). Studies have also shown that variables such as tenure moderate the different psychological aspects such as the feeling of psychological contract breach and violation (Babar, et al, 2022). Bano, et al (2022) and Khan et al (2022) argued that the relationship between social media dependency and narcissistic behavior was different for different age groups such millennials and baby boomers.…”
Section: Exploring Factors Influencing Prosocial Behavior and Life Sa...mentioning
confidence: 59%
“…This study further concluded that participants' satisfaction with the one-sided exploitation in one of games also declined with age (Matsumoto & Yamagishi, 2016). Studies have also shown that variables such as tenure moderate the different psychological aspects such as the feeling of psychological contract breach and violation (Babar, et al, 2022). Bano, et al (2022) and Khan et al (2022) argued that the relationship between social media dependency and narcissistic behavior was different for different age groups such millennials and baby boomers.…”
Section: Exploring Factors Influencing Prosocial Behavior and Life Sa...mentioning
confidence: 59%